Well-being of individuals with psoriasis in Iceland - Sara Alexandra Jónsdóttir 1988- (2019)
Psoriasis is an immune-mediated disease that causes red, scaly patches on the skin which can be very painful, irritating and disabling. Research has indicated that individuals with psoriasis have increased probability of anxiety and depression symptoms, as well as lower quality of life. The aim of this study was to explore the well-being of individuals with psoriasis in Iceland and whether higher disease severity or itch intensity (pruritus) is related to higher scores on anxiety and depression scales and lower quality of life. PASI was used to assess disease severity, the 5-D Itch Scale to assess itch intensity (pruritus), GAD-7 to measure symptoms of anxiety, PHQ-9 for symptoms of depression and SWLS to assess perceived quality of life. All participants answered an online questionnaire and consisted of 199 individuals in total, of which 131 (66.8%) were with psoriasis and 67 (33.7%) without psoriasis. Women were in great majority (84.4%), the most frequent age range was 30 – 39 years (31.2%) and almost half the participants were married. PASI total score had a significant correlation to the PHQ-9 score (r = .361) and the 5-D Itch Scale had a significant correlation to GAD-7, PHQ-9 and SWLS total scores. No significant difference was found between participants with or without psoriasis. Keywords: psoriasis, pruritus, wellbeing, anxiety, depression, quality of life. Psoriasis er langvinnur sjálfsofnæmissjúkdómur sem veldur rauðum, hreistrandi útbrotum á yfirborði húðarinnar sem geta fylgt sársauki, kláði og önnur óþægindi. Rannsóknir erlendis hafa bent til þess að einstaklingar með psoriasis séu í áhættuhópi fyrir að þróa með sér þunglyndi og kvíða en einnig á að upplifa minnkandi lífsgæði. Markmið þessarar rannsóknar var að kanna vellíðan einstaklinga með psoriasis á Íslandi og hvort alvarleiki sjúkdómseinkenna eða styrkleiki kláða hafi fylgni við fleiri kvíða og þunglyndiseinkenni, sem og lægri lífsgæði. PASI var notaður til að meta alvarleika einkenna, 5-D Itch Scale til að meta styrkleika kláða, GAD-7 til ...